2020
DOI: 10.1080/19490976.2020.1748261
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the human microbiome reveals the association between the abundance of gut bile salt hydrolases and host health

Abstract: Bile acid metabolism by the gut microbiome exerts both beneficial and harmful effects on host health. Microbial bile salt hydrolases (BSHs), which initiate bile acid metabolism, exhibit both positive and negative effects on host physiology. In this study, 5,790 BSH homologs were collected and classified into seven clusters based on a sequence similarity network. Next, the abundance and distribution of BSH in 380 metagenomes from healthy participants were analyzed. It was observed that different clusters occupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…The protein sequence similarity network (SSN) of the gut BSHs was further generated with a criterion of >40% sequence identity, which separated the gut BSHs into seven clusters ( Figure 2 a and Supplementary Figure S1 ). The classification was in accordance with that of our previous study, and we named the clusters similarly to facilitate understanding [ 16 ]. The proteins from Clusters 1 and 3 were predominantly from Bacteroidetes, consisting of 136 and 71 proteins, respectively.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The protein sequence similarity network (SSN) of the gut BSHs was further generated with a criterion of >40% sequence identity, which separated the gut BSHs into seven clusters ( Figure 2 a and Supplementary Figure S1 ). The classification was in accordance with that of our previous study, and we named the clusters similarly to facilitate understanding [ 16 ]. The proteins from Clusters 1 and 3 were predominantly from Bacteroidetes, consisting of 136 and 71 proteins, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…Our previous study suggested that the abundance of BSHs from different clusters showed distinct relationships with human diseases [ 16 ]. In this study, we mapped the gut BSH sequences in each cluster to the datasets of different diets to evaluate the relationship.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the acid-insoluble fractions of humic substances, Humic acid is partially soluble in water and form micelle-like structures in neutral to acidic conditions [2]. Humic acid is polymer compound rich in active groups such as phenolic-hydroxyl, carboxyl, sulfhydryl, and carbonyl [3,4] and is widely used in agriculture, ceramics, oil extraction, and environmental protection as an organic fertilizer, binder, mining aid, water purifier, and heavy-metal remover [5][6][7][8][9][10][11]. Humic acid is mainly found naturally in peat, lignite, and weathered coal in nature [12,13], which composition can vary according to geographical origin, age, climate and biological conditions, making the precise characterization of these substances difficult [14,15].…”
Section: Introductionmentioning
confidence: 99%